2016
DOI: 10.2308/accr-51567
|View full text |Cite
|
Sign up to set email alerts
|

Do CEO Succession and Succession Planning Affect Stakeholders' Perceptions of Financial Reporting Risk? Evidence from Audit Fees

Abstract: In this paper, we examine how CEO succession and succession planning affect perceptions of financial reporting risk among stakeholders who are responsible for and oversee firms' financial reporting (e.g., auditors, management, and audit committees). Management succession introduces uncertainty about firms' future operations, financial policies, and potential motivation for earnings management, which we predict elevates the perceived risk of financial reporting improprieties. Consistent with this prediction, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 69 publications
4
54
0
Order By: Relevance
“…Finally, to the best of our knowledge, this study is the first to explore the influence of a firm's employee quality on audit fees. Although previous studies have documented extensive evidence on the influence of a firm's personnel on audit pricing decisions, their major focus has been on the characteristics of top management (Wysocki, 2010;Beck and Mauldin, 2014;Chen et al, 2015;Bills et al, 2017;Hsieh et al, 2020). Our research departs from these studies by focusing on the overall corporate workforce and finding that auditors also incorporate the quality of a firm's employees into their engagement pricing.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, to the best of our knowledge, this study is the first to explore the influence of a firm's employee quality on audit fees. Although previous studies have documented extensive evidence on the influence of a firm's personnel on audit pricing decisions, their major focus has been on the characteristics of top management (Wysocki, 2010;Beck and Mauldin, 2014;Chen et al, 2015;Bills et al, 2017;Hsieh et al, 2020). Our research departs from these studies by focusing on the overall corporate workforce and finding that auditors also incorporate the quality of a firm's employees into their engagement pricing.…”
Section: Introductionmentioning
confidence: 89%
“…First, Call et al (2017) showed that firms operated by high-quality employees make better disclosures; that is, their financial reports are less likely to be restated. This quality of disclosure will be translated into lower audit risks in the audit engagement (Bell et al, 2001;Bedard and Johnstone, 2004;Kim et al, 2012;Bills et al, 2017). Moreover, Call et al (2017) found that internal control performed by high-quality employees is more effective.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, Bills et. al (2017) also found, through a study in U.S.A, that audited companies pay lower fees when the audit firm is performing its duties in its first three years.…”
Section: Variablesmentioning
confidence: 84%
“…Concerning the risk (RISK), this has been measured in many ways by the authors. The literature has used debt ratios, such as total liabilities to shareholders' equity (Karim & Hasan, 2012;Thinggaard & Kiertzner, 2008) and total liabilities to total assets (Naser & Nuseibeh, 2007), liquidity ratios, including the quick ratio, calculated by total current assets less total inventories divided by current liabilities (Al-Harshani, 2008;André et al, 2016;Bills, Lisic and Seidel, 2017;Fleischer & Goettsche, 2012), and the losses of previous years (Fuentes & Pucheta-Martínez, 2009;Pong & Whittington, 1994). In this study we chose the quick ratio.…”
Section: Variablesmentioning
confidence: 99%
“…Also, significantly higher audit fees are documented in the presence of high control-risk assessment (Seidel, 2017). Overall, the studies examining the dynamics of audit fees were concerned with identifying the factors and situations where such fees increase, various empirical results were documenting items of concern as: bankruptcy risk or short-selling threats (Hope et al 2017;Lennox and Kausar, 2017); firms with new CEOs (Bills et al 2017); audit effort and litigation cost in the case of foreign firms crosslisted in USA (Bronson et al 2017); litigation risk and institutional investors demands in reverse mergers (Abbott et al 2017); debt covenant violations (Jiang and Zhou, 2017). On the other hand, audit fees decrease because of competitive disadvantages, as smaller audit firms tend to charge lower audit fees (Chu et al 2018).…”
Section: Discussionmentioning
confidence: 99%